EFFECTIVENESS OF USING INJECTORS AND SALINE ON MRI IMAGE RESULTS - Ainun Anniza Jamal (Wealth Community Empowerment, 2024)
The use of Magnetic Resonance Imaging (MRI) technology with contrast media has become a standard in the world of medical diagnostics to obtain more accurate and detailed images of the body. However, the effectiveness of MRI image results does not only depend on the contrast medium. The use of injectors and saline before, during, and after the MRI imaging process plays an important role in improving the quality of the resulting images. This community service activity aims to provide education and training regarding the importance of injectors and saline in MRI procedures to medical personnel in various hospitals and clinics. Through counseling, workshops and live demonstrations, it is hoped that medical personnel can understand and apply these techniques effectively, so as to improve the accuracy of diagnosis and the quality of health services. The results of this activity show an increase in the understanding and skills of medical personnel in the use of injectors and saline, which contributes positively to the quality of MRI images and patient diagnosis results